PROBLEMS OF DAKWAH MANAGEMENT IN THE OFFICE OF RELIGIOUS AFFAIRS, TANAH PINEM DISTRICT DAIRI REGENCY - Sabri Tudar Sihotang; Waizul Qarni (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines the problems of da'wah management at the Office of Religious Affairs (KUA) in Tanah Pinem District, Dairi Regency, an area with a minority Muslim community. This study is important because da'wah management in minority areas is not only faced with religious issues, but also with limitations in human resources, worship facilities, budget support, geographical conditions, and the socio-cultural dynamics of the local community. This study aims to analyze the implementation of da'wah management functions, including planning, organizing, implementing, monitoring, and evaluating the religious development of the minority Muslim community. The study used a qualitative approach with a case study method. Data were obtained through observation, interviews, and documentation of the KUA and da'wah actors involved in religious activities in Tanah Pinem District. The results show that da'wah management has not been running optimally due to the limited number and capacity of da'i, minimal supporting facilities, low community participation, weak institutional coordination, and the dominant influence of customs and the community's economic conditions. Nevertheless, the KUA strives to strengthen da'wah through collaboration with religious leaders, a cultural approach, the use of communication media, and the development of religious instructors. The novelty of this research lies in the analysis of da'wah management through the formal institution of KUA in the context of a minority Muslim community, thus contributing to the development of a more adaptive, participatory, and contextual da'wah model.